CCTO Giant Dielectric Ceramic Prepared by Reaction Sintering. (2015) - Huang, Xinhua; Jiang, Yong; Wu, Kan
Abstract: In present research, CaCu3 Ti4 O12 (CCTO) giant dielectric ceramics were prepared by solid phase reaction sintering method. Two ways of sintering were used: 1) the sintering temperature was risen to 1100 o C directly, hold on 2, 3, 6, 8 hours respectively; 2) first, the temperature was heated to 1150 o C, then decreased to 1000 o C immediately and hold on 3, 6, 9 hours separately. The sintering performance, dielectric properties and impedance characteristics, as well as the relationship between the characteristics were investigated. The experiments show that, the density of the CCTO ceramics prepared via the first routine raised with increasing soaking time. Meanwhile the radial shrinkage rate had a significant increase. But via the second routine, the radial shrinkage rate had a slight increase. In both processes the dielectric constant and dielectric loss of all samples were decreased with the test frequency increase. With the soaking time increased, the downtrend of the dielectric constant was also found.